Diagnostic Test on Chemical Equilibrium Misconception: A Literature Review - Rosida, Nuchrurita; Widarti, Hayuni Retno; Yahmin, Yahmin (Universitas Negeri Malang, 2022)
The abstract nature of chemical equilibrium learning material tend to result in misconception. The issues of misconception are identified using multi-tier diagnostic tests. This study aims to examine previous studies investigating the multi-tier diagnostic test in investigating the misconception of chemical equilibrium. We adopted a systematic literature review using the PRISMA method in analyzing 30 scientific articles discussing chemical equilibrium misconception and their analysis methods. The results of our content analysis suggest a number of multi-tier diagnostic test types that can be used to analyze the chemical equilibrium misconception, namely the two-tier, three-tier, and four-tier diagnostic tests.